Real Time Analytics for Non-Web Based Applications - Jindal, Arvind (My University, 2015)
Enormous software applications, both web and non-web based are built by organizations as a solution to solve problems. However, in today’s competitive world providing a solution is not sufficient. One also needs to keep a track of the usage of the applications, activities being performed by the users on the application and look for the areas which if improved act as customer delight. Also, it is becoming clear that such data analytics needs to be carried out in real time for the business success. Although it is easier to track and analyze web based applications, but the same is not true for non-web based applications. In this thesis, a framework is proposed which would help one perform such real time data analytics for non-web based applications possible over cloud. The performance and accuracy of the framework is evaluated with the help of a case study. The experimental results demonstrate that this framework effectively helps provide real time data insight for non-web based applications.
M.E. (CSED)
Keywords: Real Time Analytics; Software Applications; Google Analytics; software applications; data mining; data analysis; computer science; cse